Cohort profile: Research on Obesity and Diabetes among African Migrants in Europe and Africa Prospective (RODAM-Pros) cohort study - Agyemang, Charles; van der Linden, Eva L; Antwi-Berko, Daniel; Nkansah Darko, Samuel; Twumasi-Ankrah, Sampson; Meeks, Karlijn; van den Born, Bert-Jan H; Henneman, Peter; Owusu-Dabo, Ellis; Beune, Erik (BMJ open, 2022)
PurposeThe Research on Obesity and Diabetes among African Migrants (RODAM) prospective (RODAM-Pros) cohort study was established to identify key changes in environmental exposures and epigenetic modifications driving the high burden of cardiovascular disease (CVD) risk among sub-Saharan African migrants.ParticipantsAll the participants in the RODAM cross-sectional study that completed the baseline assessment (n=5114) were eligible for the follow-up of which 2165 participants (n=638 from rural-Ghana, n=608 from urban-Ghana, and n=919 Ghanaian migrants in Amsterdam, the Netherlands) were included in the RODAM-Pros cohort study. Additionally, we included a subsample of European-Dutch (n=2098) to enable a comparison to be made between Ghanaian migrants living in the Netherlands and the European-Dutch host population.Findings to dateFollow-up data have been collected on demographics, socioeconomic status, medical history, psychosocial environment, lifestyle factors, nutrition, anthropometrics, blood pressure, fasting blood, urine and stool samples. Biochemical analyses included glucose metabolism, lipid profile, electrolytes and renal function, liver metabolism and inflammation. In a subsample, we assessed DNA methylation patterns using Infinium 850K DNA Methylation BeadChip. Baseline results indicated that migrants have higher prevalence of CVD risk factors than non-migrants. Epigenome-wide association studies suggest important differences in DNA methylation between migrants and non-migrants. The follow-up study will shed further light on key-specific environmental exposures and epigenetic modifications contributing to the high burden of CVD risk among sub-Saharan African migrants.Future plansFollow-up is planned at 5-year intervals, baseline completed in 2015 and first follow-up completed in 2021.